LINEARITY OF n-ARY ASSOCIATIVE ALGEBRAS - Harutyunyan, David N. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
In this paper n-ary regular division associative algebras are discussed. It is shown that every operation in n-ary regular division associative algebra will be endo-linearly represented over the same binary group. Schauffler like theorem will be proved for those algebras.